Visual memory and motor planning in a natural task - Hayhoe, Mary M.; Shrivastava, Anurag; Mruczek, Ryan; Pelz, Jeff B. (Journal of vision (Charlottesville, Va.), 2003)
This paper investigates the temporal dependencies of natural vision by measuring eye and hand movements while subjects made a sandwich. The phenomenon of change blindness suggests these temporal dependencies might be limited. Our observations are largely consistent with this, suggesting that much natural vision can be accomplished with "just-in-time" representations. However, we also observe several aspects of performance that point to the need for some representation of the spatial structure of the scene that is built up over different fixations. Patterns of eye-hand coordination and fixation sequences suggest the need for planning and coordinating movements over a period of a few seconds. This planning must be in a coordinate frame that is independent of eye position, and thus requires a representation of the spatial structure in a scene that is built up over different fixations.